2021
DOI: 10.3389/fevo.2021.627765
|View full text |Cite
|
Sign up to set email alerts
|

Declines in Common and Migratory Breeding Landbird Species in South Korea Over the Past Two Decades

Abstract: Population declines in terrestrial bird species have been reported across temperate regions in the world and are attributed to habitat loss, climate change, or other direct mortality sources. North American and European studies indicate that long-distance migrants, common species, and species associated with grasslands and agricultural lands are declining at the greatest rates. However, data from East Asia on avian population trends and associated drivers are extremely sparse. We modeled changes in occupancy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 116 publications
0
11
0
Order By: Relevance
“…Biodiversity is essential for ecosystems to function well and provides crucial services, impacting the economy, human health, and quality of life 1 . However, particularly in birds, biodiversity is threatened worldwide due to habitat loss, degradation, and climate change 2 . In the last 50 000 years, 10%–20% of bird species have become extinct and many more are threatened, indicating the urgency of genetic conservation 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodiversity is essential for ecosystems to function well and provides crucial services, impacting the economy, human health, and quality of life 1 . However, particularly in birds, biodiversity is threatened worldwide due to habitat loss, degradation, and climate change 2 . In the last 50 000 years, 10%–20% of bird species have become extinct and many more are threatened, indicating the urgency of genetic conservation 3 .…”
Section: Introductionmentioning
confidence: 99%
“…1 However, particularly in birds, biodiversity is threatened worldwide due to habitat loss, degradation, and climate change. 2 In the last 50 000 years, 10%-20% of bird species have become extinct and many more are threatened, indicating the urgency of genetic conservation. 3 However, the unique reproductive properties of birds make it difficult to directly apply technologies used for genetic rescue in mammals, such as in vitro fertilization and cloning; as an alternative, germline transmission has been pioneered for birds.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors may also affect the population dynamics of wintering EKs in Taiwan, such as global or regional population declines, reductions in wintering habitat or changes in wintering sites due to climate change. Monitoring at breeding sites in Northeast Asia, including Japan (Ueta and Uemura 2021), South Korea (Kim et al 2021) and China (China Ornithological Society 2008), has shown that EK populations are stable in these regions, and thus global population decline is unlikely to be the major cause of the reduced records in Taiwan. Although agricultural land in Taiwan is decreasing each year (Chiou et al 2012), the number of BWKs using the same habitat type continues to increase, suggesting that reduced wintering habitat is also not the major reason.…”
Section: Possible Reasons For the Vulnerability Of Eurasian Kestrelsmentioning
confidence: 99%
“…Due to limited monitoring data, the population trends of the majority of forest‐dependent migratory birds in EAAF are unavailable. Exceptions are studies in Japan and South Korea, where the distributions of several forest‐dependent long‐distance migrants are declining based on breeding atlas data (Amano & Yamaura, 2007; Kim et al, 2021; Yamaura et al, 2009). Notably, in these studies, the population decline of migratory birds were seldomly identified with corresponding forest loss in its breeding area, which are consistent with our findings.…”
Section: Regional Conservation Implications In East Asiamentioning
confidence: 99%
“…A lack of population trend and threat assessments is putting the migratory landbirds of the East Asian‐Australasian Flyway (EAAF) under threat (Kim et al, 2021; Ueta & Uemura, 2021; Yong et al, 2021). Although it is highly species diverse, supporting the highest number of threatened species among the five global highways (Kirby et al, 2008), very little is known about the population trends of EAAF migratory landbirds (Kim et al, 2021; Newton, 2007; Yong et al, 2021). Such an information gap can result in the late detection of severe population decline (Stanton, 2014).…”
Section: Introductionmentioning
confidence: 99%